Efficacy of Heated Glove Liners - Santee, William R.; Blanchard, Laurie A.; Mullen, Stephen P. (2000)
Total handwear insulation (IT) is dependent on the rate of heat transfer in air through the skin-handwear interface, handwear layers, and the surface boundary air layer. Increasing air velocity reduces the insulation (Ia) provided by the boundary layer. As altitude increases, the corresponding decrease in air pressure and viscosity reduces convective heat loss. It should therefore increase. The issue Light-duty glove (LD), Trigger-finger mitten (TF) and Arctic Mitten (AM), were tested as 2-layer systems at simulated altitudes of sea level, 2500 m and 5000 m in still air and at 5 m s-1 on a biophysical hand model. Overall, the effects of wind and altitude on IT were significant. Differences between 0 and 5000 m were significant, except for AM. Increases in IT greater than 10% are considered of sufficient magnitude to alter comfort sensation. Differences of that magnitude occurred most frequently between 0 and 5000 m, and least frequently between 2500 and 5000 m. The present results are consistent with an exponential drop in insulation with increasing altitude. Changes in IT were greater in still air and for less insulated handwear where the contribution of Ia to IT was more important.